The usage of blockchain in business - Grebennikov A. I. (Scientific studies and modern education, 2019)
today, the topic of blockchain is at the peak of fashion. Any project causes increased interest if it is «on the blockchain», any newspaper article attracts additional attention if it mentions this technology. But many people do not fully understand what this technology is, how it works and where it can be used. In this article, we want to speculate about how blockchain can be used in business and show why this technology can really change our future for the better.
Keywords: financial market; финансовый рынок; криптовалюта; cryptocurrency; блокчейн; blockchain; технологии в бизнесе; technologies for business